2014
DOI: 10.1369/0022155414531437
|View full text |Cite
|
Sign up to set email alerts
|

Human Eosinophil Leukocytes Express Protein Disulfide Isomerase in Secretory Granules and Vesicles

Abstract: SummaryProtein disulfide isomerase (PDI) has fundamental roles in the oxidative folding of proteins in the endoplasmic reticulum (ER) of eukaryotic cells. The study of this molecule has been attracting considerable attention due to its association with other cell functions and human diseases. In leukocytes, such as neutrophils, PDI is involved with cell adhesion, signaling and inflammation. However, the expression of PDI in other leukocytes, such as eosinophils, important cells in inflammatory, allergic and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…MYDGF co-localized most extensively with P4HB (ER marker) around the periphery of the nucleus and in the centralized patch between nuclear lobes, with overlapping immuno-staining accounting for over 90% of staining relative to either antibody alone in unactivated or IL5-activated eosinophils ( Table 1). The immuno-fluorescence pattern of P4HB is consistent with previous immuno-gold electron microscopic studies of eosinophils that localized P4HB to the nuclear envelope (11). MYDGF in the patch co-localized with RCAS1, a Golgi marker (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…MYDGF co-localized most extensively with P4HB (ER marker) around the periphery of the nucleus and in the centralized patch between nuclear lobes, with overlapping immuno-staining accounting for over 90% of staining relative to either antibody alone in unactivated or IL5-activated eosinophils ( Table 1). The immuno-fluorescence pattern of P4HB is consistent with previous immuno-gold electron microscopic studies of eosinophils that localized P4HB to the nuclear envelope (11). MYDGF in the patch co-localized with RCAS1, a Golgi marker (Fig.…”
Section: Resultssupporting
confidence: 90%
“…When we realized that C19orf10 had been characterized functionally as MYDGF (9), we asked whether eosinophils represent a second myeloid source of releasable MYDGF. As described herein, however, upon immuno-staining of eosinophils we found that MYDGF did not localize to eosinophil granules but rather to the Golgi and endoplasmic reticulum (ER), which in eosinophils is restricted to the nuclear envelope (11).…”
Section: Introductionsupporting
confidence: 51%
“…5a), MBP 17 (Fig. 6a) and PDI 27 (Fig. 6b), within human leukocytes isolated from the peripheral blood.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…17,24,26) and protein disulfide isomerase (PDI) 27 in leukocytes. We demonstrated that CD9 is abundant on the surface of eosinophil leukocytes, presenting the first EM data of the ultrastructural immunolocalization of CD9 in human eosinophils, which represents a novel insight into the organization of the antigen presentation complex of these cells 24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation